Selective Targeting of Cancer Cells by Copper Ionophores: An Overview - Oliveri, Valentina (Frontiers in Molecular Biosciences, 2022)
Conventional cancer therapies suffer from severe off-target effects because most of them target critical facets of cells that are generally shared by all rapidly proliferating cells. The development of new therapeutic agents should aim to increase selectivity and therefore reduce side effects. In addition, these agents should overcome cancer cell resistance and target cancer stem cells. Some copper ionophores have shown promise in this direction thanks to an intrinsic selectivity in preferentially inducing cuproptosis of cancer cells compared to normal cells. Here, Cu ionophores are discussed with a focus on selectivity towards cancer cells and on the mechanisms responsible for this selectivity. The proposed strategies, to further improve the targeting of cancer cells by copper ionophores, are also reported.